2022
DOI: 10.1038/s41467-022-28693-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical control of nuclear import by Importin-7 is regulated by its dominant cargo YAP

Abstract: Mechanical forces regulate multiple essential pathways in the cell. The nuclear translocation of mechanoresponsive transcriptional regulators is an essential step for mechanotransduction. However, how mechanical forces regulate the nuclear import process is not understood. Here, we identify a highly mechanoresponsive nuclear transport receptor (NTR), Importin-7 (Imp7), that drives the nuclear import of YAP, a key regulator of mechanotransduction pathways. Unexpectedly, YAP governs the mechanoresponse of Imp7 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 143 publications
0
29
0
Order By: Relevance
“…On top of this mechanism, indirect effects mediated for instance by changes in importin α levels (Extended Data fig. 3) or by competition between cargoes for importin binding (as recently demonstrated between YAP and importin 7 65 ) may play a role in different contexts.…”
Section: Discussionmentioning
confidence: 93%
“…On top of this mechanism, indirect effects mediated for instance by changes in importin α levels (Extended Data fig. 3) or by competition between cargoes for importin binding (as recently demonstrated between YAP and importin 7 65 ) may play a role in different contexts.…”
Section: Discussionmentioning
confidence: 93%
“…For example, both dnKASH 33 expression and Sun1/2 co-depletion 34 decrease nuclear β-Catenin levels. In the case of Yap, dnKASH expression 35 and depletion of Nesprin1 36 both inhibit nuclear translocation through nuclear pore complexes in response to mechanical stimulus, potentially by limiting cytoskeleton-induced nuclear deformations, or by impairing association with Yap's nuclear transporter, Importin 7 37 . LINC-mediated cytoskeletal connections also affect deformations of the inner nuclear membrane: for example, it dnKASH expression reduces stretching of LaminA/C measured via FRET-based LaminA/C force sensor 38 , and decreases the chromatin deformations during cardiomyocyte contractions 39 .…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of proteins are identified to contain the monopartite classical importin α NLS sequences, KRRR and KRKXK ( 50 57 ). Recently, using a bio-informatics approach, based on bibliographic and simulation data, and experimental in vitro validation, we have presented the sequence EKRKI(E/R)(K/L/R/S/T) as a recognition motif for binding with Importin 7 ( 58 ), a result recently confirmed by another group ( 59 ) while recent data [( 60 ) under review] identified the sequences LPPRS(G/P)P and KP(K/Y)LV as recognition motifs for importins 4 and 5 binding, respectively.…”
Section: Introductionmentioning
confidence: 78%